Successful versus unsuccessful instrumental deliveries—Predictors and obstetric outcomes. (January 2020) - Elfituri, Abdullatif; Datta, Tamal; Hubbard, Harry R.; Ganapathy, Ramesh
Abstract: Objective: The purpose of this study was to examine instrumental births in a multi-ethnic population to assess the factors associated with success and failure in instrumental births. Study design: This was a large retrospective study of 7954 women that underwent either a successful or an unsuccessful instrumental delivery in a single centre over a 10 year period. Results: Logistic regression analysis showed that women with a BMI of more than 30, attempted Forceps delivery, having a prolonged second stage, Macrosomia (birth weight more than 4 kg) and a senior obstetrician performing the procedure increase the risk of a failed instrumental delivery. While age, ethnicity, type of anaesthesia, use of oxytocin or induction of labour did not provide a significant outcome. Results also showed that patients are likely to bleed more and neonates need admission in failed instrumental deliveries when compared to successful attempts. Conclusion: This is one of a very few studies comparing a large cohort of successful instrumental births with unsuccessful attempts at an instrumental birth. The rate of failure has been difficult to reduce, and the analysis shows that many of the factors associated with failure are not modifiable in labour. We should consider studies with use of ultrasound assessment before application or consideration of instruments to facilitate birth. This will allow us to objectively come up with an algorithm to predict success or failure and consider if it is suitable to attempt an instrumental birth. Our data can be used to counsel women about the difficulty in predicting success and failure rate of instrumental births.